The inhibitory activity of herbal medicines on the keys enzymes and steps related to carbohydrate and lipid digestion - Sompong, Weerachat (BMC Complement Altern Med, 2016)
BACKGROUND: Obesity and overweight are consistently associated with metabolic disorders including hyperglycemia and hyperlipidemia. Herbal medicines have been currently suggested as an alternative source of potentially useful antihyperglycemic, antihyperlipidemic, antioxidant activities. The objective of this study was to assess the in vitro inhibitory effects of eleven herbal medicines on carbohydrate and lipid digestive enzymes and the key steps of lipid digestion including the inhibition of micelle formation and the ability to bind bile acid. In addition, antioxidant activity of herbal medicines was also investigated. METHODS: α-Glucosidase, pancreatic α-amylase, pancreatic lipase, and pancreatic cholesterol esterase inhibitory activities of aqueous extract of herbal medicines were measured using the enzymatic colorimetric assay. The formation of cholesterol micelles was determined using the cholesterol assay kit. The bile acid binding was measured using the colorimetric assay. Antioxidant activities were assessed by using four methods including Trolox equivalent antioxidant capacity (TEAC), oxygen radical absorbance capacity ORAC), superoxide radical scavenging activity (SRSA), and hydroxyl radical scavenging activity (HRSA). RESULTS: The extracts (1 mg/mL) markedly inhibited intestinal maltase (5.16 − 44.33 %), sucrase (1.25–45.86 %), pancreatic α-amylase (1.75–12.53 %), pancreatic lipase (21.42–85.93 %), and pancreatic cholesterol esterase (2.92–53.35 %). The results showed that all extracts exhibited the inhibitory activity against pancreatic lipase with the IC(50) values ranging from 0.015 to 4.259 mg/mL. In addition, the incorporation of cholesterol into micelles was inhibited by the extracts (6.64–33.74 %). The extracts also bound glycodeoxycholic acid (9.9–15.08 %), taurodeoxycholic acid (12.55–18.18 %), and taurocholic acid (11.91 − 18.4 %). Furthermore, the extracts possessed various antioxidant activities including the TEAC values (0.50 − 4.70 μmol trolox/mg dried extract), the ORAC values (9.14–44.41 μmol trolox/mg dried extract), the SRSA (0.31 − 18.82 mg trolox/mg dried extract), and the HRSA (0.05–2.29 mg trolox/mg dried extract). The findings indicated that Syzygium aromaticum, Phyllanthus amarus, Thunbergia laurifolia were the effective promising antihyperglycemic and antihyperlipidemic agents. Statistical analysis demonstrated strong positive significant correlations between the contents of phenolic compounds and % inhibition of pancreatic lipase (r = 0.885, p < 0.001), % inhibition of pancreatic cholesterol esterase (r = 0.761, p < 0.001), and the TEAC value (r = 0.840, p < 0.001). Furthermore, there was a strongly positive correlation between the TEAC value and % inhibition of pancreatic cholesterol esterase (r = 0.851, p < 0.001) and % inhibition of pancreatic lipase (r = 0.755, p < 0.001). CONCLUSIONS: Three herbal medicines including Syzygium aromaticum, Thunbergia laurifolia, and Phyllanthus amarus markedly inhibited the intestinal α-glucosidase, pancreatic α-amylase, pancreatic lipase, and pancreatic cholesterol esterase. They also reduced formation of cholesterol micelle and bound bile acid. The findings indicate that these herbal medicines might be a promising agent for antihyperglycemic, antihyperlipidemic, and antioxidant activities.